2022
DOI: 10.1007/s10803-022-05474-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Initial Efficacy of an Adapted Telepractice Listening Comprehension Intervention for School-Aged Children with Autism

Abstract: This study evaluates the feasibility and initial efficacy of an 11-week listening comprehension intervention, Building Vocabulary and Early Reading Strategies (BVERS) that was delivered remotely to 14 elementary-aged children with autism spectrum disorder. Children were randomly assigned to one of two groups: BVERS only, or BVERS with a parent instructional component (BVERS + PC). Results indicate that the intervention was feasible to implement. All parents were satisfied with intervention implementation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Instructional intensification such as repeated exposure, specific modeling, longer duration or more frequent dosage of lessons, and frequent cumulative review and practice, have all been found to be beneficial for students with ID when developing reading skills. Recent studies have found that students with ID, including ID and autism, can develop reading skills beyond just sight word memorization, including decoding and language comprehension skills (Afacan et al, 2018;Browder et al, 2008;Conner et al, 2022;Henry et al, 2022;Lemons et al, 2015Lemons et al, , 2017.…”
Section: Reading Instruction For Children With Autism and Cognitive D...mentioning
confidence: 99%
“…Instructional intensification such as repeated exposure, specific modeling, longer duration or more frequent dosage of lessons, and frequent cumulative review and practice, have all been found to be beneficial for students with ID when developing reading skills. Recent studies have found that students with ID, including ID and autism, can develop reading skills beyond just sight word memorization, including decoding and language comprehension skills (Afacan et al, 2018;Browder et al, 2008;Conner et al, 2022;Henry et al, 2022;Lemons et al, 2015Lemons et al, , 2017.…”
Section: Reading Instruction For Children With Autism and Cognitive D...mentioning
confidence: 99%